Before she disappeared ebook - Gardner, Lisa (Frankie Elkin, 2021)
THE INSTANT NEW YORK TIMES BESTSELLER From #1 New York Times bestselling author Lisa Gardner, a propulsive thriller featuring an ordinary woman who will stop at nothing to find the missing people that the rest of the world has forgotten Frankie Elkin is an average middle-aged woman, a recovering alcoholic with more regrets than belongings. But she spends her life doing what no one else will—searching for missing people the world has stopped looking for. When the police have given up, when the public no longer remembers, when the media has never paid attention, Frankie starts looking. A new case brings her to Mattapan, a Boston neighborhood with a rough reputation. She is searching for Angelique Badeau, a Haitian teenager who vanished from her high school months earlier. Resistance from the Boston PD and the victim's wary family tells Frankie she's on her own—and she soon learns she's asking questions someone doesn't want answered. But Frankie will stop at nothing to discover the truth, even if it means the next person to go missing could be her.